Pool-based electricity market model for Malaysia electricity supply industry considering minimum generation capacity payment - Ngadiron, Zuraidah (2018)
Malaysia is improving its electricity supply industry to become more transparent, productive and competitive with the introduction of the single buyer market model. However, since the electricity demand is lower than the reserved capacity, the implementation of this market model does not provide transparent competition as Tenaga Nasional Berhad (TNB) has suffered massive profit erosion because of monthly capacity payment that should be paid to Independent Power Producers (IPP) regardless of electricity usage. Since 2005, the Malaysia Electricity Supply Industry (MESI) has planned to change to the pool market model as it is recognized as a model which could overcome the shortcomings of the single buyer market model. However, there are a few issues on introducing the pool model such as price fluctuation and market power exercises which could influence the welfare of generators as well as the consumers. Some researchers have developed pool-based market models with the aim to overcome the aforementioned issues, but the efficiency and the energy price offered from the generators are not considered. Therefore, this research developed a model introducing the minimum generation capacity payment involving the efficiency of the generators and base load sharing approaches. The proposed model was tested using the 2, 16 and 24 generator test systems involving IPPs and Tenaga Nasional Berhad Generation (TNBG) around Peninsular Malaysia for an economic analysis to highlight the merits of the proposed model in terms of generation revenue and demand payment. The results have shown that the proposed market model ensures the intermediate value of total generation revenue which decreased from 1.99% to 4.67% and 3% to 9.62% during the weekday and weekend, respectively. The demand payment decreased as it is proportional to the generation revenue. However, this proposed model did not consider market uncertainties. This findings can be applied for MESI and globally, in assisting and creating a new policy to achieve a better electricity market model.